Analysis of the Effect of the Oil Palm Harvest Bonus System on Employee Performance and Job Satisfaction - Khairunnisyah Nasution; Surya Dharma; Dian Hendrawan (Postgraduate, University of Mataram, 2025)
Productivity and labor quality are fundamental outcomes of applied science implementation in agribusiness systems, particularly within plantation-based vocational and contextual learning environments. In applied science education, real-world work settings function as living laboratories where scientific principles, management practices, and human resource strategies are directly translated into measurable performance outcomes. The oil palm plantation sector provides a highly relevant context for such learning, as it integrates biological production systems, operational management, and incentive-based decision-making that are central to vocational science education and workforce competency development. Within this context, remuneration mechanisms especially harvest bonus systems serve not only as managerial instruments but also as applied learning models that shape workers’ understanding of productivity targets, performance standards, and economic accountability in practical field conditions. Using a proportionate stratified random sampling method, 38 respondents were selected to represent different work tenure levels. Data were collected through questionnaires and analyzed using descriptive and simple linear regression techniques. The results show that the task-based bonus system significantly affects both employee performance and job satisfaction, with positive regression coefficients indicating that higher bonuses lead to improved productivity, attendance, and work quality. Furthermore, employees perceived the reward system as fair and motivating, contributing to higher morale and engagement. Overall, the study concludes that a well-structured and transparent reward mechanism strengthens employee motivation and enhances organizational performance in oil palm plantations.